Camera shy? Motivations, attitudes and beliefs of bird photographers and species-specific avian responses to their activities. (September 2019) - Slater, Caitlin; Cam, Graham; Qi, Yin; Liu, Yang; Guay, Patrick-Jean; Weston, Michael A.
Abstract: Bird photography is a popular and growing pursuit which may disturb birds. This study: 1) characterises photographer motivations, attitudes and behaviours; and, 2) examines avian escape responses evoked by photographers. Bird photographers ( n  = 188) answered scaled questions with responses characterised using Principle Components Analysis. Photographers had high commitment and specificity to bird photography, often documenting species rarity or novelty, but rarely videoed birds. Respondents generally thought that photography instilled an appreciation of birds in others . They were concerned with especially sensitive contexts for photography (breeding, migrating and some habitats) yet believed disturbance caused is ephemeral and trivial . Flight-Initiation Distance (FID) evoked by experimental approaches to four treatments, three of which mimicked photographer behaviour (taking an image every five steps while 1. walking, 2. walking and using a flash, 3. crouching) and 4. walkers (control) ( n  = 1093; 128 species) revealed a significant interaction between species and treatment. Single species models ( n  = 11, where n  ≥ 4 for all treatments) revealed differences between treatments for eight species. In all but one of these species, photographer behaviour was associated with longer FIDs, suggesting birds judged such behaviour as especially threatening, perhaps because aspects were similar to the behaviour of a predator. The FIDs reported here could usefully underpin enhanced guidelines for ethical bird photography, but prescriptions need to be species-specific, and tailored to the behaviours used by photographers. Graphical abstract: Unlabelled Image Highlights: We describe photographer motivations, attitudes and behaviours. Photographers took and shared images partly to inspire others. Bird photography may disturb birds. Photographers felt disturbance they caused was trivial. We quantify avian escape responses evoked by photographers. For most species, photographers evoked escape at longer distances than walkers.